Replicability in psychological research: a reflection - Centeno-Leyva, Sharon (2020)
Background: In recent years, psychological science has suffered a crisis of confidence that has been marked by the low rate of replicability demonstrated in collaborative projects that attempted to quantify this problem, evidencing the difficulty in making replications and the existence of a possible excess of false positives published in the scientific literature. Method: This opinion article aimed to review the panorama of the replicability crisis in psychology, as well as its possible causes. Conclusions: It began from the state of the replicability crisis, then some possible causes and their repercussions on the advancement of psychological science were highlighted, discussing various associated issues, such as individual biases on the part of researchers, the lack of incentives to replicability studies and the priority standards that journals would currently have for novel and positive studies. Finally, the existing alternatives to reverse this situation are mentioned, among them the opening to new statistical approaches, the restructuring of incentives and the development of editorial policies that facilitate the means for replication.